T30. PREDICTORS OF INTERNALIZED MENTAL HEALTH STIGMA IN A HELP-SEEKING SAMPLE OF ADOLESCENTS AND YOUNG ADULTS EXPERIENCING EARLY PSYCHOSIS: THE ROLES OF PSYCHOSIS-SPECTRUM SYMPTOMS AND FAMILY FUNCTIONING. (18th May 2020) - DeLuca, Joseph; Shan, LeeAnn; Jay, Samantha; Redman, Samantha; Petti, Emily; Lucksted, Alicia; Rakhshan Rouhakhtar, Pamela; Edwards, Sarah; Reeves, Gloria; Schiffman, Jason
Abstract: Background: The onset of psychosis-spectrum symptoms may be challenging to young people who are developing their identity. Internalized mental health stigma–the internalization of negative mental illness stereotypes (e.g., believing stereotypes to be true and applying them to yourself)–can lead to secrecy, shame, and withdrawal. Family factors can impact individuals who are experiencing early psychosis, but more work is needed to understand the relationship between family factors and stigma. One objective of this study was to examine if there were differences in internalized stigma across diagnostic groups. Another objective of this study was to better understand the predictors of internalized stigma among youth, particularly understudied aspects of youth stigma such as family functioning and specific types of psychosis-spectrum symptoms (e.g., positive symptoms). Methods: Participants aged 12–25 (N = 68; Mean age = 16.41, SD = 2.88) were recruited from community providers, clinics, hospitals, and schools in Maryland, USA. Participants were classified as meeting criteria for clinical high risk for psychosis (51%), early psychosis (24%), or help-seeking controls (25%). The sample was predominantly White (53%), followed by Black/African-American (19%), Biracial/Multiracial (18%), and Asian (10%). Psychosis-spectrum symptoms and depressive symptoms were measured via the clinician-administered Structured Interview for Psychosis-Risk Syndromes (SIPS) and family functioning (e.g., cohesion, support) was measured via the self-reported Family Assessment Device. Internalized stigma was measured using the self-reported Internalized Stigma of Mental Illness (ISMI) scale. ANOVA was used to test for differences in internalized stigma between high risk, early psychosis, and help-seeking controls. Multiple regression was used to evaluate predictors of internalized stigma. Results: Initial analyses indicated that there were no significant differences between the three diagnostic groups (F = 1.50, p = .23), but that clinical high risk for psychosis participants had the highest endorsement of internalized stigma (η2 = .05). Regression analyses indicated that unusual thought content/delusional ideas (one type of psychosis-spectrum positive symptom experiences measured by the SIPS), depressive symptoms, and lower family functioning significantly predicted (p < .05) higher internalized stigma, controlling for other psychosis-spectrum positive symptom experiences. These variables explained 26% of the variance in ISMI in the model (F = 4.01, p = .001). Negative, disorganized, and general SIPS items (except depression), as well as age, gender, race/ethnicity, relationship status, family history of psychosis, and income level, were unrelated to ISMI. Discussion: This is the first study to assess the relationship between family functioning, psychosis-spectrum symptoms, and internalized stigma among youth. Youth endorsement of unusual thought content/delusional ideas, depressed mood, and lower family functioning were associated with more self-reported internalized stigma from mental health concerns. Better understanding the predictors of internalized stigma among youth can lead to more tailored and effective treatment approaches. This study suggests that a particular focus on certain positive symptoms and family functioning may be warranted in the treatment of internalized stigma. Future research is needed to determine the temporal precedence and nature of the impact of these factors on ISMI, in addition to the potential differential impact of family factors by race/ethnicity and culture.